A aprendizagem baseada na resolução de problemas no ensino de lançamento oblíquo - Carvalho, Fábio Roberto de (2017)
The active methodologies of teaching become increasingly present in the various fields and levels of education, being adopted for enabling the overall development of the learner, not only of their academic knowledge, but also of skills necessary for the development of their own life in society. Thus, the present study aims to apply the methodology of Problem - Based Learning in the oblique release content, which is included in the official curriculum of the first year of São Paulo state high school. For its accomplishment a first year high school class of a school participant of the program of integral education was chosen, whose objectives are in agreement with the proposals of the methodology used. The planning was elaborated taking into account the curricular extension and the availability of pedagogical resources of the school unit. The result of the work was investigated through the application of questionnaires, whose objectives and results are available in the present study. The work was very positive to the development of the students, especially regarding the motivation and dedication, characteristics not very apparent in the methodology that was being used. The work also proved to be very important to the development of the author, both in knowledge by presenting it a teaching methodology of which he identified and felt fulfilled, as well as in personal development by helping him overcome old frustrations with the completion of his Masters.